Um estudo comparativo do perfil de valores pessoais entre estudantes de gradua????o em administra????o de empresas e gestores profissionais. - Leite, Rogeryo (2013)
Values may be understood as principles, concepts and beliefs that defines what is important, essential for someone. Values guide the definition of personal goals and they serve as references on which the ways of achievement of the desired state are defined. At the university, all the process of socialization among students brings so much contribution for the learning process as the theories and cognitive abilities transmitted for them. In that environment personal values are shared and the same happens in the business environment where most of students intend to be after finishing the course and want to achieve success. This research made a comparison of personal values of business students and business professional managers, considering the fact that the business courses intend to develop well prepared managers for the companies. This comparison was made between managers and students that shows good performance in terms of grades or in terms of socialization, by social network analysis.